Turning a blind eye: Meritocracy moderates the impacts of social status on corruption perception. (24th November 2020) - Tan, Xuyun; Zhang, Yue; Liu, Li; Dou, Xuejiao; Gu, Zibei; Liang, Yuan; Dang, Jianning
Abstract : Findings on the effect of social status on corruption perception are mixed. To make sense of the mixed results, three studies were conducted to examine whether meritocracy moderates this effect. In Study 1, we measured all variables using a questionnaire‐based correlational design. In the preregistered Study 2, we adopted an experimental design in which we manipulated social status using a false feedback paradigm and measured corruption perception and meritocracy. In Study 3, we manipulated meritocracy using a scrambled sentence task and measured its effect on the relationship between social status and corruption perception. The results consistently demonstrated that meritocracy could moderate the influence of social status on corruption perception. Specifically, social status was negatively associated with corruption perception when meritocracy was weak, whereas the association was not significant when meritocracy was strong. Our results suggest that meritocracy critically affects acknowledgment of the pervasiveness of social injustice and even deters the disadvantaged from fighting against corruption.